Immunologic mechanisms in systemic lupus erythematosus - Fong, Kok-Yong (Henry Stewart Talks, 2010)
Several immunologic mechanisms are involved in the pathogenesis of systemic lupus erythematosus, The immune cells (T cells, B cells) are activated, and release various cytokines as well as autoantibodies, Results in facilitation of the inflammatory process and organ damage, The exact pathogenic mechanisms are still not fully known
Archived at 2018/05/31